Decoupling Control Strategy of BLIM considering Rotor Mass Eccentricity - Wenshao Bu; Biao Li; Chunxiao Lu (Journal of Control Science and Engineering)
A BLIM, i.e., bearingless induction motor, is a multivariable, nonlinear, and strong coupling object; to achieve its high performance magnetic suspension operation control and overcome the influence of the rotor mass eccentricity, a decoupling control strategy considering the rotor mass eccentricity is proposed. Firstly, the mathematical model of the torque system based on the rotor flux orientation and the mathematical model of the magnetic suspension system based on the air gap flux orientation are presented; on this basis, the inverse system decoupling control method of the BLIM is researched. Then, according to the frequency characteristics of the unbalanced displacement, an unbalance vibration compensator is designed, which can generate a compensation force to suppress or eliminate the unbalanced displacement. Simulation experimental results have shown that the decoupling control among the rotor flux-linkage, motor speed, and two radial displacement components can be achieved; in the steady state, the unbalanced displacement can be basically eliminated, while, during the mutation process of motor speed, the unbalanced displacement can be suppressed effectively.